Liver enzyme concentrations as measure of possible infectivity in chronic asymptomatic carriers of hepatitis B. Issue 6152 (9th December 1978) - Barbara, J A; Mijovic, V; Cleghorn, T E; Tedder, R S; Briggs, M
Abstract : Fifty-two British-born blood donors who were chronic carriers of hepatitis B surface antigen (HBsAg) were tested for the presence of hepatitis B e antigen (HBeAg) and antibody to HBeAg by an immunoradiometric assay. The presence of HBeAg was closely associated with a slight rise in serum liver enzyme concentrations, a high HBsAg titre, and male sex. We suggest that the finding of persistently raised serum liver enzyme concentrations in an asymptomatic HBsAg carrier might be useful as a likely indicator of HBeAg and high infectivity.